PEMASARAN BERBASIS E-COMMERCE PADA PRODUK VIRGIN COCONUT OIL (VCO) KELURAHAN GAMTUFKANGE - Rosdiana Rosdiana; Tamrin Husaen (JURNAL PENGABDIAN MANDIRI, 2022)
Partners wish to introduce VCO products to a wider audience of their target market through targeted online promotional activities, but because the knowledge and skills of partners in e-commers-based marketing are still lacking, training from competent and competent human resources is needed. mastering e-commerce-based marketing techniques so that the latest menus from e-commerce applications can be used and the products offered are widely known in the market. The purpose of community service is to increase partners' knowledge about e-commerce-based marketing because until now partners are still very difficult in marketing products because these products are not widely known by the public. The method used is the extension method to increase understanding of a problem that is closely related to the soft skills and hard skills possessed by partners regarding e-commerce-based marketing. The results of the PKM obtained are that partners are very enthusiastic in learning e-commerce-based marketing so that partners can quickly understand what has been conveyed by the presenter and can immediately practice it, therefore this PKM activity is very important to carry out.